Data borders : how Silicon Valley is building an industry around immigrants - Villa-Nicholas, Melissa (University of California Press, 2023)
"Data Borders investigates entrenched and emerging borderland technology that ensnares all people in an intimate web of surveillance where data resides and defines citizenship. Detailing the new trend of biologically mapping undocumented people through biotechnologies, Melissa Villa-Nicholas shows how surreptitious monitoring of Latinx immigrants is the focus of and driving force behind Silicon Valley's growing industry within defense technology manufacturing. Villa-Nicholas reveals a murky network that gathers data on marginalized communities for purposes of exploitation and control that implicates law enforcement, Border Patrol, and ICE, but that also pulls in public workers and the general public, often without their knowledge or consent. Enriched by interviews of Latinx immigrants living in the borderlands who describe their daily use of technology and their caution around surveillance, this book argues that in order to move beyond a heavily surveilled state that dehumanizes both immigrants and citizens, we must first understand how our data is being collected, aggregated, correlated, and weaponized with artificial intelligence and then push for immigrant and citizen information privacy rights along the border and throughout the United States"--